Brain cognitive comparison of fabric touch on human glabrous and hairy skin. Issue 3 (February 2016) - Wang, Qicai; Yu, Weidong; Chen, Kemin; Zhang, Zhongwei; Asad, Rabie AM
The glabrous and hairy skin of the human body contains different types of mechanoreceptive afferents. At present, consumers and researchers usually use hands (the glabrous palm) to evaluate and study the contact perception of fabric, which mainly contains two aspects of fabric performance, handle and comfort. However, in use, fabric in most cases contacts the hairy skin of the human body, rather than the glabrous skin. In order to investigate the cognitive differences in the brain for fabric touch on the two types of skin, we used the same silk fabric to touch the palm and forearm of nine subjects, and observed the brain responses simultaneously using functional magnetic resonance imaging. The results showed that for palm stimulation, activations were mainly evoked in somatosensory cortices, and deactivation in the insula cortex and, in contrast, for forearm stimulation, more activations were evoked in the insula cortex, and deactivation mainly in the primary somatosensory cortex. It is suggested that there are more sensory information arising from fabric touch on the glabrous skin, and more emotional information on the hairy skin. Therefore, for discriminating the physical properties (e.g. fabric hand) of fabric, it is better to receive fabric touch using glabrous skin, and for evaluating the emotional perception (e.g. fabric comfort) of fabric touch, it is better using hairy skin.